Cultural Sensitivity in Sámi Tourism : A Systematic Literature Review in the Finnish Context - Saari, Ritva; Hockert, Emily; Kugapi, Outi; Lüthje, Monika; Mazzullo, Nuccio (Matkailututkimus, 2020)
CAFÉ UArctic Theme (Circumpolar Archives, Folkore and Ethnography) Peer reviewed